2010
DOI: 10.1111/j.1600-0714.2009.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Minichromosome maintenance‐7 and geminin are reliable prognostic markers in patients with oral squamous cell carcinoma: immunohistochemical study

Abstract: The mean LIs for MCM7 were 29.2% for normal epithelia, 32.2% for dysplasias, and 51.1% for OSCCs; the value was significantly higher in the last than in the former two (P < 0.01). The mean LIs for geminin were 6.8% for normal epithelia, 9.2% for dysplasias, and 21.3% for OSCCs; the value was significantly higher in the OSCCs (P < 0.01). The MCM7 LIs were correlated with the histological grade of OSCCs, in which the highest LIs were noted in the poorly differentiated type (P < 0.01). The survival rate was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 32 publications
7
26
0
1
Order By: Relevance
“…We previously demonstrated the prognostic signifi cance of geminin in human colorectal and oral cancers [19,27]. Other studies have reported the potential prognostic signifi cance of geminin in breast, kidney, brain, and oral tumors [15,12,28,29], in line with our results.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We previously demonstrated the prognostic signifi cance of geminin in human colorectal and oral cancers [19,27]. Other studies have reported the potential prognostic signifi cance of geminin in breast, kidney, brain, and oral tumors [15,12,28,29], in line with our results.…”
Section: Discussionsupporting
confidence: 83%
“…However, Shrestha et al [28] reported that higher geminin LIs might be associated with longer survival in patients with high-grade astrocytic tumors with preoperative chemotherapy. We also found that higher geminin LIs were associated with better prognoses in patients with stage III-IV oral squamous cell carcinoma receiving preoperative radiochemotherapy [27]. These confl icting results could be explained by an increase in radiochemosensitivity associated with geminin overexpression; some studies have shown that cells synchronized in G1 phase were more radioresistant than cells in the S, late G2, and M phases [31,32].…”
Section: Discussionmentioning
confidence: 57%
“…It has been suggested that Geminin might provide useful information about tumor proliferation activities that is equal or superior to that of MCM proteins or Ki-67. Moreover, there have been many studies demonstrating that immunohistochemical analysis with the combination of MCM proteins, Ki-67, and Geminin may be useful for predicting tumor proliferating activities or patient prognosis in various malignancies (5,11,14,15,17,37). These findings are consistent with the present study, in which tumors that are positive for all of MCM7, Ki-67, and Geminin possess high proliferation potential, resulting in a high ratio of poorly differentiated and locally invasive tumors in phenotype II.…”
Section: Discussionsupporting
confidence: 82%
“…After DNA replication is initiated during the cell cycle, Geminin inhibits re-uploading of the MCM proteins onto chromatin, thus preventing DNA re-replication in the same cell cycle (13). It has been confirmed that these proteins are useful biomakers that reflect the proliferative activity of the tumor cells and predict the survival of patients Multiparameter analysis using cell cycle biomarkers for small-size lung adenocarcinoma : Prognostic implications TOMOHIRO HARUKI 1,2 , KOHEI SHOMORI 1 , TATSUSHI SHIOMI 1 , YUJI TANIGUCHI 2 , HIROSHIGE NAKAMURA 2 and HISAO ITO 1 1 with various types of cancer (5)(6)(7)(8)(9)(10)(11)(14)(15)(16)(17)(18). Aurora A, known as a member of the serine/threonine kinase family, controls a subset of critical mitotic events including centrosome maturation and separation, as well as chromosome orientation and segregation (19).…”
Section: Introductionmentioning
confidence: 99%
“…MCM2 to MCM7, form an important complex; its regulation is essential to DNA replication. 11,12 It has been recently demonstrated that entry into the quiescent state causes rapid disappearance of Ki-67, followed by the disappearance of MCM3 expression. 13 This indicates that the assessment of these proteins may be a useful tool to establish which cells are proliferating and which are resting.…”
mentioning
confidence: 99%